2023
DOI: 10.3390/sym15030778
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Attribute Decision Making Based on Intuitionistic Hesitant Fuzzy Connection Set Environment

Abstract: The intuitionistic hesitant fuzzy set (IHFS) is an enriched version of hesitant fuzzy sets (HFSs) that can cover both fuzzy sets (FSs) and intuitionistic fuzzy sets (IFSs). By assigning membership and non-membership grades as subsets of [0, 1], the IHFS can model and handle situations more proficiently. Another related theory is the theory of set pair analysis (SPA), which considers both certainties and uncertainties as a cohesive system and represents them from three aspects: identity, discrepancy, and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We will further investigate our novel techniques in the scope of multi-criteria development in the fuzzy environment and examine the idea behind our suggested methods within the perspective of square root fuzzy information [47,48]. Additionally, we will examine our ongoing research using a temporal intuitionistic fuzzy system [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…We will further investigate our novel techniques in the scope of multi-criteria development in the fuzzy environment and examine the idea behind our suggested methods within the perspective of square root fuzzy information [47,48]. Additionally, we will examine our ongoing research using a temporal intuitionistic fuzzy system [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Ghorui, N. et al [13] identified the dominant risk factor involved in the spread of COVID-19 using hesitant fuzzy MCDM methodology. In addition to medical diagnosis, a great deal of study in other areas [14,15] involving hesitant fuzzy sets has been carried out. Additionally, many studies have been conducted on generalized fuzzy numbers, including generalized triangular intuitionistic fuzzy numbers (GTIFN) [16], generalized trapezoidal hesitant fuzzy numbers (GTrHFN) [2], generalized hesitant fuzzy numbers (GHFN) [8], and generalized hexagonal fuzzy numbers (GH χ FN) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Example 3. Let consider ∆1 , ∆2 , ∆3 and ∆4 are four GDHH χ FNs define as ∆1 =<(5,6,7,8,9,10); {(0.7, 0.2), (0.9, 0.05), (0.85, 0.1)} >, ∆2 =< (0.1, 0.2, 0.3, 0.6, 0.7, 0.8); {(0.8, 0.15), (0.75, 0.2), (0.9, 0)} >, ∆3 =< (0.60, 0.65, 0.75, 0.85, 0.95, 1); {(0.9, 0.05), (0.75, 0.2), (0.85, 0.1)} > and ∆4 =<(9,10,12,14,16,17); {(1, 0), (0.9, 0.05), (0.8, 0.15)} >.…”
mentioning
confidence: 99%
“…Moving forward, our future investigations will delve into the application of our novel techniques in the realm of multi-criteria development within the fuzzy environment. We will also explore the underlying concept of intuitionistic hesitant fuzzy connection information [51,52] in relation to our suggested methods. Additionally, our ongoing research involves the utilization of a temporal intuitionistic fuzzy system [53][54][55] as an avenue for further exploration.…”
Section: Introductionmentioning
confidence: 99%